Tagatose Suppresses Grapevine Powdery Mildew and Downy Mildew under Field Conditions with No Severe Impacts on Grape Must Fermentation - O. Giovannini; T. Roman; A. Nesler; I. Pertot; M. Perazzolli (Australian Journal of Grape and Wine Research, 2022)
Background and Aims. Grapevine is susceptible to several diseases and requires a large use of fungicides. Sustainable alternatives must be safe for humans and the environment and also should not interfere with must fermentation. The aim of this study was to implement the use of a rare sugar, tagatose, against powdery mildew and downy mildew and to assess possible side effects on Saccharomyces cerevisiae fermentation. Methods and Results. Tagatose was evaluated for the suppression of powdery mildew and downy mildew under controlled and field conditions and for its impact on S. cerevisiae fermentation of synthetic and grape musts. Tagatose applied at 8 kg/hareduced powdery mildew and downy mildew severity and incidence on grapevine leaves and bunches under field conditions. Tagatose caused a limited and transient slowdown of the fermentation with no negative impact on yeast viability and wine chemical composition at the end of the fermentation. Conclusions. Tagatose is a promising alternative for sustainable grapevine protection against powdery mildew and downy mildew with no negative impacts on the must fermentation. Significance of the Study. These findings pave the way for grapevine protection strategies based on the use of rare sugars as sustainable fungicides in integration with other plant protection products.